Estudo clínico randomizado sobre a eficácia da polihexanida no tratamento da mucosite oral em pacientes com câncer de cabeça e pescoço. - Andrade, Ana Paula Eufrázio do Nascimento (2016)
Introduction: Malignant neoplasms represent one of the main causes of morbi-mortality in Brazil and worldwide. Radiotherapy, whether associated or not with chemotherapy, is the therapeutic modality most often used for cancer of the head and neck. However, it can trigger reactions at the oral level, such as oral mucositis, the most limiting side effect, with intense pain and difficulty eating, which may require the suspension of oncologic treatment for the patient. Polyhexanide has been used effectively and safely in the treatment of acute and chronic wounds. Objectives: To describe the clinical-epidemiologic profile and investigate the efficacy of polyhexanide in the treatment of oral mucositis and pain relief, in the period of 8-15 days, among patients with cancer of the head and neck undergoing treatment with radiotherapy (whether associated or not with chemotherapy). Methods: A randomized clinical trial was conducted, parallel and double-blind, among patients with cancer of the head and neck undergoing radiotherapy treatment with or without chemotherapy, in the High Complexity Oncology Unit of Feira de Santana, Bahia, who developed oral mucositis, were 18 years of age or older and consented to participation and signed informed consent forms in the period of July 2015 to May 2016. Two equal groups were formed by random allocation—an intervention group (polyhexanide gel) and a control group (gel without polyhexanide). These groups were reevaluated after 8 and 15 days of use of the gels. Clinical exams, evaluations of the medical records, and interviews with the application of a survey instrument used in the study were approved by the Committee for Ethics in Human Subjects Research of the State University of Feira de Santana, under the number 1.074.479/2015. Statistical analysis consisted of relative and absolute frequencies, averages, medians, and standard deviation, and the p-value—considered statistically signification when <0.05—were obtained by non-parametric Friedman tests, Wilcoxon the posts with signs and Wilcoxon-Mann-Whitney. Results: The findings were presented as an article. The mean age was 59.68 years; 58.8% men; 67.6% Brown/Black, and 79.4% with an elementary school education or less. The majority of tumors (64.7%) already presented in advanced stage, and the most frequent were those of the pharynx (23.5%) and the oral cavity (20.4%). Radiotherapy associated with chemotherapy was the most used therapy. Grades III and IV of oral mucositis were the most frequent in the third and fourth weeks of radiotherapy treatment. A total of 34 individuals were accompanied, 17 in the intervention group and 17 in the control group. After a period of 8 to 15 days, statistically significant differences were observed (p<0.05) in relation to the reduction in severity of the oral mucositis and pain, between the time points of gel use in the intervention group. Conclusions: Knowledge of the clinical-epidemiologic profile of patients undergoing oncology treatment with oral mucositis is important to establish potentially effective treatments. In this study polyhexanide represented an effective therapy in the treatment of oral mucositis and relief of pain, with positive results in the first 8 days of use.